Results in Fixed Point Theorems of Ordered B-Metric Spaces ‎for Rational Type ‎ a‎-Admissible Contractive Mappings - Raji, Muhammed; Ibrahim, Musa Adeku; Kehinde, Rotimi (International Journal of Advanced Mathematical Sciences, 2025)
In this paper, we present a rational type ‎ ‎-Admissible contraction mappings in the context of partially ordered b-metric spaces and leverage ‎on it to establish the existence and uniqueness of fixed point theorems for self-mappings within the framework of complete partially ordered ‎b-metric spaces. The results of this article are applied to determine the solution to an integral equation. Through illustrative examples, we ‎showcase the practical applicability of the results, demonstrating their effectiveness in real-world scenarios‎.